Hubungan RTH dengan PDRB dalam Pemodelan Sistem Dinamik di Jakarta - James Sinurat (IJEEM - Indonesian Journal of Environmental Education and Management, 2017)
The objective of this research is to find out the availability of green open space (GOS) in the long run by prediction as a result of the increase of Gross Regional Domestic Product (GRDP), and to choose an appropriate scenario to fulfil the availability of GOS, through system dynamic modeling in Jakarta. The modeling of system dynamic with regard to GOS and GRDP, data collection of secondary data and primary data through interpretation of satellite image is expected to solve the problem of the availability of GOS. Based on simulation scenario, the result of the research showed that the availability of GOS became lesser year by year as a result of the increase of GRDP. In order to secure the availability of GOS accordingly with the regulatiaon of Space Management, the scenario that should be executed is the very optimistic scenario.